Vocational Guidance in the Republic of Lithuania - Beresnevičienė, Danguolė (Acta Paedagogica Vilnensia, 2002)
The article deals with the problem of understanding of the terms: „vocation" „vocational guidance" „vocational orientation", which meaning were changing during the time and according to the theories of different researchers in this field. The aim of the article is to analyse the research and understanding of „vocational orientation" in Re- public of Lithuania from 1919 till 1938 years and to evaluate the results and impact of these researches in nowadays understanding of vocational guidance. The results of the article show, that presumptions of appearance of the theory and research on vocational guidance in Lithuania were made in the end of XJX century and beginning of XX century, when Lithuanian publicists and enlighteners analysed the questions of Adult Education and the conditions, influenced their choosing of vocation. The activity of Lithuanian research in the time of Independence of Lithuania (from 1919 till 1938 year) was very high and a lot of their ideas (necessity to evaluate labour market needs, to predict it in the process of vocational guidance of youth, to help pupils to know more about the psychological and psychophysiological requirements of the vocations, etc.,) are very useful even today, when Educational Reform in Lithuania is going on. The recommendations for nowadays teachers and researchers of vocational guidance is included in the article.